Analysis of the temperature effect on concrete crosstie flexural behavior. (30th January 2019) - Canga Ruiz, Alvaro E.; Qian, Yu; Edwards, J. Riley; Dersch, Marcus S.
Highlights: Temperature at top and base of concrete crossties are linearly related to ambient. Change in support conditions due to temperature gradient affects flexural behavior of crossties. Relation between temperature gradient and bending moment variation under train loading is linear. Curling due to temperature gradient can increase flexural demand up to 38 kip-in at center and rail seats. Temperature gradient can lead to a reduction of the flexural capacity of concrete crossties as high as 21%. Abstract: The manner in which temperature affects concrete components or structures has been studied extensively for many applications, such as pavements, bridges, and frames. However, little attention has been given to the temperature effects on concrete railroad crossties. Recent research at the University of Illinois at Urbana-Champaign revealed the relationship between temperature gradient and curling on freight railroad concrete crossties, which showed that temperature gradient could change the support conditions of the crossties, affecting their flexural performance. This paper presents the results from an extensive field study of temperature effects on the flexural behavior of rail transit concrete crossties, part of a larger research program aimed at designing more efficient and resilient concrete crossties for rail transit applications. Field instrumentation was installed on light, heavy, and commuter rail systems to monitor temperature variation and corresponding concrete crosstie flexural behavior for up to 10 months at each location. A linear relationship between the temperature in the crosstie and the ambient temperature is observed. Additionally, the bending moment distribution under revenue service loading conditions is found to be directly affected by the temperature gradient between top and bottom of the crosstie. This effect is believed to be a consequence of the variation in the support condition due to curling, and is thought to be independent of the crosstie design or loading environment. A linear correlation between the temperature gradient variation in the crosstie and the flexural behavior of the crosstie is observed. A maximum difference of 38 kip-in (4.29 kN-m) for the center negative bending moment of the concrete crosstie was found due to a change in the temperature gradient from −10 °F (−5.6 °C) to 37 °F (20.6 °C), which represents 21% of the design capacity. Based on the analysis of field observations, a correction factor of 1 kip-in/°F (0.203 kN-m/°C) is recommended to account for the temperature gradient as a design variable for future rail transit concrete crossties.